Outbreak investigation of food poisoning attributed to Omphalotus japonicus using polymerase chain reaction‐based sequencing - Ting, Man‐Ju; Lin, Cheng‐Lu; Chen, Hsiang‐Ling; Chou, San Fang; Jaw, Fu‐Shan; Tsai, Kuang‐ Chau; Hsieh, Chien‐Chieh (Hong Kong journal of emergency medicine, 2024)
Objective This study aims to report and analyse an outbreak of Omphalotus japonicus poisoning following mushroom ingestion in Taiwan, and to employ PCR methods for accurate identification of the toxic mushrooms involved. Methods A descriptive observational study was conducted involving a family of four who ingested the mushrooms in the mountainous rural area of Yilan County, Taiwan. Data were collected through interviews with the affected individuals and a review of their medical records. Due to the destruction of the mushroom samples, Polymerase Chain Reaction (PCR) methods were utilized for identification. Genomic DNA was extracted from the raw fruiting bodies, and specific primers targeting the internal transcribed spacer region of the nuclear ribosomal DNA were designed for PCR detection. Results Three family members (mother, daughter, and son) experienced gastrointestinal symptoms, including nausea, vomiting, abdominal cramps, and diarrhea, approximately 30 min after consuming the mushrooms. Upon admission to the emergency room, they were hydrated and monitored, with laboratory results showing slightly elevated alanine transaminase levels. The affected individuals recovered within 12 h and were discharged in good condition on day 2. PCR analysis of the mushroom sample confirmed the identification of Omphalotus japonicus, known to produce Illudin S and Illudin M, which cause acute gastrointestinal symptoms. This case represents the first documentation of using PCR‐based sequencing to diagnose Omphalotus japonicus poisoning in the English literature.